Relations between Household- and Neighborhood-Level Social and Economic Factors and Parent-Reported Behavior in Children with Neurofibromatosis Type 1 - (:unkn) unknown (My University, 2024)
A growing body of research acknowledges the role of children’s socioeconomic contexts in their development. However, in children with neurodevelopmental disorders, these factors remain relatively unexplored. This thesis examines the relations between family- and neighborhood-level socioeconomic factors and parent-reported behavior in children with NF1. Results indicated that greater maternal education, as a proxy for household socioeconomic status, was associated with fewer difficulties with attention, social skills, symptoms of developmental social disorders, executive functioning, externalizing symptoms, behavior problems, and adaptive skills. Holding maternal education constant, neighborhood socioeconomic deprivation was associated with greater difficulties with attention and social skills. The relationship between neighborhood socioeconomic factors and social skills was dependent on NF1 status, such that children with NF1 were more susceptible to the deleterious effects of neighborhood deprivation on social development compared to their unaffected siblings and peers. Exploratory analyses revealed that the relationship between neighborhood socioeconomic deprivation and parent-reported behavior was not dependent on NF1 etiology. These findings contribute to the present understanding of socioeconomic inequity as a determinant of children’s psychosocial health.
Keywords: Psychology; Developmental psychology; Attention; Child Opportunity Index; Neighborhood deprivation; Neurofibromatosis type 1; Social skills; Socioeconomic status